Developing Microlearning Writing Materials for Grade X Students of Senior High School - Kusumaningrum, Monika Cahya; Priyana, Joko (PT FORMOSA CENDEKIA GLOBAL, 2025)
The lack of interactive writing materials presents a challenge for Grade X students at SMAN Yogyakarta. This study aimed to identify students’ writing needs, develop suitable microlearning-based materials, and determine appropriate content and design. Using the ADDIE model in an R&D framework, 36 students from Class X-H participated. Data were gathered through surveys, interviews, and questionnaires. Results show that students prefer everyday topics and engaging media, especially YouTube videos, to enhance vocabulary, grammar, and text structure. They also value materials that are clear, simple, and relevant. Expert judgment and classroom trials confirmed that the developed microlearning materials are appropriate for writing skills.